2016
DOI: 10.1097/md.0000000000002523
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Internal Limiting Membrane Flap For Large Traumatic Macular Holes

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…Satisfactory results expanded the use of this technique to myopic MH, traumatic MH, repeat MH surgery, and optic disc maculopathy. 7,[15][16][17][18] Yamashita et al compared conventional ILM peeling and inverted flap technique in both medium-large (400-550µm) and extra-large (>550µm) MHs. They reported the closure rate of 95% and 100% in medium-large MHs by conventional and inverted flap techniques, respectively, and 88% and 100% in extra-large MHs although the difference between the two techniques was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfactory results expanded the use of this technique to myopic MH, traumatic MH, repeat MH surgery, and optic disc maculopathy. 7,[15][16][17][18] Yamashita et al compared conventional ILM peeling and inverted flap technique in both medium-large (400-550µm) and extra-large (>550µm) MHs. They reported the closure rate of 95% and 100% in medium-large MHs by conventional and inverted flap techniques, respectively, and 88% and 100% in extra-large MHs although the difference between the two techniques was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Like most studies, Hou and Jiang reported that 48 (89%) of the 54 eyes with TMH were successfully closed with visual acuity significantly improved after vitrectomy [ 39 ], but Yuan et al did not find significant improvement of visual function in the 18 (69.2%) of 26 cases of TMH that were successfully closed with vitrectomy and gas tamponade [ 31 ]. Literature reported outcomes of vitrectomy for cases series of TMH which are summarized in Table 3 [ 6 , 31 , 33 , 36 , 39 – 50 ]. This review shows that the anatomic success rate ranges from 45% to 100%, with a median of 92.5%; functional success (2 or more lines' improvement) rate ranges from 27% to 100%, with a median of 84%.…”
Section: Vitrectomymentioning
confidence: 99%
“…Shousha assessed the role of inverted ILM flap as a treatment option for large TMHs. In a prospective noncomparative study of 12 eyes with large TMHs (basal diameter of 1300–2800 um), a 100% closure rate and improvement of best-corrected visual acuity were achieved 6 to 9 months after the surgery [ 50 ].…”
Section: Vitrectomymentioning
confidence: 99%
“…In der Vergleichsstudie von Borʼi et al (2017) betrug der bestkorrigierte Visus 0,3 ± 0,25 in der Silikonöl-Gruppe und 0,2 ± 0,13 in der Gas-Gruppe [44]. Der invertierte ILM-Flap als adjuvante Maßnahme während der ppV hat bei 12 Augen zu einem anatomischen Verschluss von 100 % und zu einem medianen bestkorrigierten Visus von 20/100 geführt [45]. [44].…”
Section: Pars-plana-vitrektomieunclassified
“…Ikeda et al (2002) wiesen auf die Effektivität des ILM-Peelings mit ppV für TMF mit retinalen Falten hin [50]. In einer weiteren Studie führte der invertierte ILM-Flap als adjuvante Maßnahme in Kombination mit der ppV bei 12 Augen mit großen TMF (Durchmesser: 1300-2800 µm) zu einem anatomischen Verschluss von 100 % und zu einem medianen bestkorrigierten Visus von 20/100 [45].…”
Section: Vitrektomie Bei Kindernunclassified